2017
DOI: 10.1002/hep.29133
|View full text |Cite
|
Sign up to set email alerts
|

PRMT5 restricts hepatitis B virus replication through epigenetic repression of covalently closed circular DNA transcription and interference with pregenomic RNA encapsidation

Abstract: PRMT5 restricts HBV replication through a two-part mechanism including epigenetic suppression of cccDNA transcription and interference with pregenomic RNA encapsidation; these findings improve the understanding of epigenetic regulation of HBV transcription and host-HBV interaction, thus providing new insights into targeted therapeutic intervention. (Hepatology 2017;66:398-415).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
150
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 115 publications
(153 citation statements)
references
References 39 publications
1
150
0
2
Order By: Relevance
“…A growing body of evidence suggests that histone modifications on cccDNA regulate the viral transcription. The HBc and HBx proteins, H3 and H4 histones, cellular transcription factors (CREB [cAMP response element‐binding protein], activating transcription factor, YY1 [Yin Yang 1], signal transducer and activator of transcription [STAT] 1, and STAT2), and chromatin modification enzymes (PCAF [p300/CBP‐associated factor]/GCN5 [general control nonderepressible 5], p300/CBP [CREB‐binding protein], HDAC1, SIRT1 [sirtuin 1], protein arginine methyltransferase [PRMT] 1, PRMT5, and EZH2 [enhancer of zeste homolog 2]) have been shown to be associated with cccDNA by using chromatin immunoprecipitation assays (Fig. ).…”
Section: Epigenetic Control Of Hbv Infectionmentioning
confidence: 68%
See 2 more Smart Citations
“…A growing body of evidence suggests that histone modifications on cccDNA regulate the viral transcription. The HBc and HBx proteins, H3 and H4 histones, cellular transcription factors (CREB [cAMP response element‐binding protein], activating transcription factor, YY1 [Yin Yang 1], signal transducer and activator of transcription [STAT] 1, and STAT2), and chromatin modification enzymes (PCAF [p300/CBP‐associated factor]/GCN5 [general control nonderepressible 5], p300/CBP [CREB‐binding protein], HDAC1, SIRT1 [sirtuin 1], protein arginine methyltransferase [PRMT] 1, PRMT5, and EZH2 [enhancer of zeste homolog 2]) have been shown to be associated with cccDNA by using chromatin immunoprecipitation assays (Fig. ).…”
Section: Epigenetic Control Of Hbv Infectionmentioning
confidence: 68%
“…EZH2 is a subunit of PRC2 and has the KMT activity on H3K27. Interestingly, a recent study showed that knockdown of EZH2 resulted in up‐regulation of HBeAg and HBsAg, indicating a repressive function of EZH2 on HBV gene expression . H3K122ac is enriched at genetic elements associated with transcriptionally active genomes in vivo and is catalyzed by the transcriptional coactivator, p300/CBP .…”
Section: Epigenetic Control Of Hbv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…cccDNA is complexed with cellular histone and non-histone proteins, assembling in to chromatin like structures, as has been called a mini-chromosome (Bock et al, 1994, 2001; Newbold et al, 1995). Enrichment of host RNA pol II on cccDNA has been reported to be associated with active posttranscriptional modifications (PTMs) on ccc-DNA bound histone (Riviere et al, 2015; Zhang et al, 2017). …”
Section: Transcription Of Cccdna and Transport Of Rna Out Of The Nucleusmentioning
confidence: 99%
“…There is active co-recruitment of cellular histone acetyltransferases-p300/CBP and PCAF/GCN5- and the histone deacetylases (HDAC1 and hSirt1) and polycomb repressor complex (EZH2 and YY1) in vivo and in vitro onto cccDNA that correlate with high and low viral replication, respectively (Belloni et al, 2009, 2012). In other attempts to study the histone methylation status of cccDNA and regulation of its transcription, PRMT5 (protein methyltransferase 5) has been shown to induce a symmetric di-methylation of H4R3 on cccDNA and regulate the binding of host pol II and host Brg1-based hSW1/SNF chromatin remodeler contributing to the transcriptional repression RNA of cccDNA (Zhang et al, 2017); in addition, hSirt3 was found to restrict HBV cccDNA transcription by acting cooperatively with histone methyltransferase SUV39H1 to decrease the recruitment of SETD1A, leading to a marked increase of H3K9me3 and a decrease of H3K4me3 on cccDNA (Ren et al, 2018). …”
Section: Transcription Of Cccdna and Transport Of Rna Out Of The Nucleusmentioning
confidence: 99%